PERSEPSI KARIR MAHASISWA MANAJEMEN PARIWISATA ISLAM SELAMA DAN SETELAH PANDEMI COVID-19 - Puput Yanita Senja (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The Covid-19 pandemic has affected the workforce in the tourism industry. This has resulted in tourism students as the future workforce of the tourism industry being forced to consider career plans. The uncertain situation causes uncertainty in the perception of students' careers. Therefore, the authors wanted to compare the perceptions of students concentrating on tourism management during and after the Covid-19 pandemic. This study used a qualitative method approach and used an online qualitative survey. The results showed that there were differences in student career perceptions during and after the pandemic. The pandemic has had an impact on the tourism industry workforce. The work environment is required to implement health protocols, decrease salaries and benefits, and the workforce requires more skills and competencies such as foreign language and IT skills. After the pandemic, the work environment in the tourism industry returns to normal. Salaries and benefits continue to increase. The competencies and skills needed include communication, foreign language skills, digital technology, and high dedication to advancing the tourism industry. Career support is needed by students from campus in the form of holding Field Work Lectures, holding workshops to prepare for entering the world of work, and building an entrepreneur center.